Eksplorasi Permainan Rakyat dan Olahraga Tradisional Bambu dalam Pemajuan Kebudayaan Desa Kebonsari, Magelang - Lestari, Afifa; Setiawati, Yuli; Hasyim, Fuat (Jurnal Pemberdayaan Pariwisata, 2025)
Kebonsari Village, located in Borobudur District, Magelang, is lag ging behind other villages in terms of tourism due to its inability to fully leverage its existing potential. The village's abundant natural bamboo resources play an important role in various aspects of community life socially, economically, educationally, and culturally. Traditional games and sports (PROT) made from bamboo have strong appeal in developing education-based tourism in Kebonsari. Therefore , assistance wa provide to develop bamboo-based educational tourism through the branding initiative Kampoeng Dolanan Pring Kebonsari. The program included several activities: identification meetings to comprehensively document existing PROT; DGtS to introduce traditional games to a wider audience; trial travel patterns to train the community in hosting tourists; a traditional games festival to foster cultural pride; and the creation of tourism packages as a means to develop educational tourism rooted in folk games. This initiative represents an effort to advance culture through a community-based approach that emphasizes sustainability and the stability of natural ecosystems . Keywords:  PROT, tourism village, OPK, bamboo, community